2015
DOI: 10.1016/j.ab.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Bone protein extraction without demineralization using principles from hydroxyapatite chromatography

Abstract: Historically, extraction of bone proteins has relied on the use of demineralization to better retrieve proteins from the extracellular matrix; however, demineralization can be a slow process that restricts subsequent analysis of the samples. Here, we developed a novel protein extraction method that does not use demineralization, but utilizes a methodology from hydroxyapatite chromatography where high concentrations of ammonium phosphate and ammonium bicarbonate are used to extract bone proteins. We report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
3
42
0
2
Order By: Relevance
“…This result is similar to our previous results detecting only the N-terminal peptide of OC from human samples without prior purification in the presence of a large number of collagen I peptides. [49] Removal/depletion of the collagen I or enrichment of osteocalcin by purification [37] may help to better identify this protein from bone samples by MS.…”
Section: Resultsmentioning
confidence: 99%
“…This result is similar to our previous results detecting only the N-terminal peptide of OC from human samples without prior purification in the presence of a large number of collagen I peptides. [49] Removal/depletion of the collagen I or enrichment of osteocalcin by purification [37] may help to better identify this protein from bone samples by MS.…”
Section: Resultsmentioning
confidence: 99%
“…In either case, for studies specifically seeking NCPs in low protein samples (e.g., osteonectin in fossils) it is imperative that any demineralization fractions be analyzed rather than discarded, regardless of comparatively minute amounts of extract. Conversely, extraction protocols that do not include a separate demineralization stage (e.g., Cleland & Vashishth, 2015; Hill et al, 2015) may be particularly well suited for the recovery of NCPs from fossils, and should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…For samples in which analysis of a separate demineralization fraction is not feasible, alternative methods that do not fractionate demineralization, or do not demineralize (e.g., Cleland & Vashishth, 2015; Hill et al, 2015), should be considered to avoid loss of identified protein diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Two sets of fragments from the nasal turbinates (sample 1, 19.5 mg; sample 2, 19.8 mg) of NYSM VP-47 were homogenized with a Bead Ruptor 24 (Omni International) using the non-demineralization buffer from [20] to extract proteins. The turbinates were chosen because this skull has an apparent varnish on the entire exterior (figure 2) that does not appear to have been applied within the nasal cavity.…”
Section: (B) Protein Extractionmentioning
confidence: 99%